The Dynamics of Human Rights Issue Resolution from the Perspective of Dignified Justice - Kuncoro, Owen Edgar; Riyanto, Tio; Wilbert, Reyner (Inovasi Pratama Internasional. Ltd, 2025)
Human rights are important to uphold because they guarantee the principle of equality for all people. There may be some citizens who are less aware of the importance of human rights for themselves. There are many human rights violations that occur in Indonesian society, human rights themselves are regulated in the Pancasila legal system. The purpose of the law itself includes 3 things, namely the value of justice, benefit, and legal certainty. The value of justice is the most important value in law. The research method that we use in our journal is a literature review or analysis research method and also uses normative analysis of laws, court decisions, and policies that cover everything about human rights. The purpose of our research is to provide a dignified justice perspective on Human Rights in accordance with the dynamics of constitutional law. We hope that this journal can increase public awareness of the importance of human rights for humans and can also build greater justice in human rights for society.